2015
DOI: 10.5755/j01.ms.21.3.7352
|View full text |Cite
|
Sign up to set email alerts
|

Formation of High Temperature Compounds in W-C-B System by Reactive Spark Plasma Sintering

Abstract: The formation of high temperature composites in W-C-B system from fine-grained powders in dependence on the ratio of components by using reactive spark plasma sintering was studied. The mixture of W2C and C nanoparticles was used as tungsten and carbon precursors. The W2C and carbon mixture with different ratio of components was prepared by reduction of WO3 in presence of CH4 in nitrogen inductively coupled plasma. The specific surface area of the mixture was in the range of 36-42 m 2 /g in dependence on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…As one kind of boride and silicide composite, WB-WSi 2 composites are promising as advanced structural materials. There are only few attempts for sintering of tungsten boride in the literature [19][20][21][22]. Grabis et al fabricated WB 2 and B 4 C composites by spark plasma synthesis from W 2 C, C and amorphous B blends [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one kind of boride and silicide composite, WB-WSi 2 composites are promising as advanced structural materials. There are only few attempts for sintering of tungsten boride in the literature [19][20][21][22]. Grabis et al fabricated WB 2 and B 4 C composites by spark plasma synthesis from W 2 C, C and amorphous B blends [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are only few attempts for sintering of tungsten boride in the literature [19][20][21][22]. Grabis et al fabricated WB 2 and B 4 C composites by spark plasma synthesis from W 2 C, C and amorphous B blends [20]. Kuzenkova et al studied pressureless sintering of W 2 B 5 at 1700 ºC and indicated that W 2 B 5 phases decomposed into WB and B (which was further oxidized) phases [21].…”
Section: Introductionmentioning
confidence: 99%